2021
DOI: 10.21203/rs.3.rs-770278/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel Long-noncoding RNA LncZFAS1 prevents MPP+-induced neuroinflammation through MIB1 activation

Abstract: Parkinson’s disease remains one of the leading neurodegenerative diseases in developed countries. Despite well-defined symptomology and pathology, the complexity of Parkinson’s disease prevents a full understanding of its’ etiological mechanism. Mechanistically, α-synuclein misfolding and aggregation appears central for disease progression, but mitochondrial dysfunction, dysfunctional protein clearance and ubiquitin/proteasome systems, and neuroinflammation have also been associated with Parkinson’s disease. P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Recently, Qin et al reported that MIB1 overexpression relieved apoptosis and inflammation of cardiac microvascular endothelial cells during coronary microvascular dysfunction by targeting the ASK1/p38 pathway [72]. In agreement with the hypothesis, lncZFAS1 overexpression directly interfered with mir590-3p to inhibit TXNIP the MIB1 E3 ubiquitin ligase/NLRP3 pathway [6]. Finally, we consider that LncZFAS1 can be used as an important regulatory target for neuroinflammatory pathways in PD.…”
Section: Interaction Between Lncrna Zfas1 and Mirnas In Pd Neuroimmun...supporting
confidence: 88%
See 4 more Smart Citations
“…Recently, Qin et al reported that MIB1 overexpression relieved apoptosis and inflammation of cardiac microvascular endothelial cells during coronary microvascular dysfunction by targeting the ASK1/p38 pathway [72]. In agreement with the hypothesis, lncZFAS1 overexpression directly interfered with mir590-3p to inhibit TXNIP the MIB1 E3 ubiquitin ligase/NLRP3 pathway [6]. Finally, we consider that LncZFAS1 can be used as an important regulatory target for neuroinflammatory pathways in PD.…”
Section: Interaction Between Lncrna Zfas1 and Mirnas In Pd Neuroimmun...supporting
confidence: 88%
“…NLRP3 is an inflammatory complex mainly present in microglia and contains a caspase activation recruitment domain and caspase-1, which promotes the secretion of IL-1/ IL-18 and induces pyroptosis to destroy microglia to further release IL-1 [36][37][38]. Our results showed that SH-SY5Y cells generated and activated NLRP3 to induce cellular pyroptosis [6], revealing the role of NLRP3 and cells other than microglia in the neuroinflammatory response in PD. Besides, NLRP3 inflammasome activation may aggravate dopaminergic neuronal loss in Parkinson's disease [39].…”
Section: The Role Of Nlrp3 In Pd Neuroimmunologymentioning
confidence: 76%
See 3 more Smart Citations